Assessing environmental security in China. Issue 7 (2nd July 2014) - Grumbine, R Edward
Abstract : In recent decades, perspectives on the integrated social–ecological aspects of natural resource problems have become increasingly influential as traditional national security outlooks have expanded to include environmental and human concerns. However, China has not been influenced much by new environmental security frameworks. An overview of six main stressors – ecosystem degradation, food security, energy, water, urbanization, and climate change – that affect security in China reveals that current policies need to be reformed. China's ecosystems remain subject to widespread degradation, food supply is under stress, energy demand is growing rapidly, there are increasing conflicts over water quality and quantity, urbanization cannot proceed without fundamental environmental and social reforms, and climate‐change impacts are projected to intensify. To resolve such security issues, China's leaders must depend less on technological solutions and should instead craft adaptive management reforms to address the lack of interdisciplinary problem‐solving, low institutional capacity, and gaps between policy and implementation.